ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEKERJA MIGRAN PERMANEN DI KOTA DENPASAR - Putri, Ni Made Ayu Askarimi; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 5 (2022): VOL 11 NO 5, MEI 2022 [1621-2044]DO - 10.24843/EEP.2022.v11.i05.p03, 2022)
Permanent population displacement already has enough work to meet their daily needs. This study to analyze 1) Work experience, working hours, number dependents and work status have simultaneous effect on income permanent migrant workers in Denpasar City. 2) Work experience, working hours, number dependents and work status partially affect the income permanent migrant workers in Denpasar City. 3) which factors among work experience, working hours, number dependents and work status have the most dominant influence on income permanent migrant workers in Denpasar City. This study uses observation as 111 permanent migrant workers for respondents. This study uses multiple linear regression analysis techniques. The results of this study indicate 1) Work experience factors, working hours, number of dependents and work status have a simultaneous effect on the income of permanent migrant workers in Denpasar City. 2) Factors of work experience, working hours, number of dependents and employment status partially have a positive effect on the income of permanent migrant workers in the city of Denpasar. 3) Migrant workers with formal employment status earn higher incomes than migrant workers with informal employment status. Keywords: Work Experience, Working Hours, Number of Dependents, Job Status, Income.